Money, income, and profit: lessons from the monetary theory of production - Carrera, Andrea; Rossi, Sergio (Iberian Journal of the History of Economic Thought, 2015)
In this paper we analyze Augusto Graziani’s numerous contributions to the monetary theory of production, which he developed from a theoretical but also a policy-oriented perspective. We focus on the rejection of the neoclassical dichotomy, the causal relation between production and money creation, and the definition of macroeconomic saving. These three dimensions of Graziani’s work can be identified in the framework of the monetary circuit, in the tradition of classical and Marxian economic thought. The outcome of Graziani’s investigations sheds light on the working of a monetary economy of production from the issuance of bank money to the distribution of income and capital accumu-lation.